A REVOLTA DE ESPÁRTACO: ABORDAGEM SEMIÓTICA DE UMA FONTE LITERÁRIA - de Araújo, Sônia Regina Rebel (PHOÎNIX, 2020)
This paper offers an analysis of aspects of the Spartacus rebellion, as put forwards in Plurarch's Crassus, 8-11, by the systematic approach of the semiotics of language.